MCM-41-immobilized 1, 10-phenanthroline–copper(i) complex: a highly efficient and recyclable catalyst for the coupling of aryl iodides with aliphatic alcohols. Issue 88 (7th September 2016) - Lin, Yang; Cai, Mingzhong; Fang, Zhiqiang; Zhao, Hong
Abstract : A practical method for the synthesis of aryl alkyl ethers has been developed by heterogeneous Cu-catalyzed C–O coupling. Abstract : A heterogeneous C–O coupling reaction between aryl iodides and aliphatic alcohols was achieved in neat alcohol or toluene at 110 °C in the presence of 10 mol% of the MCM-41-immobilized 1, 10-phenanthroline–copper(i ) complex [MCM-41-1, 10-phen–CuI] with Cs2 CO3 as a base, yielding a variety of aryl alkyl ethers in good to excellent yields. The new heterogeneous copper catalyst can easily be prepared by a simple procedure from commercially available and inexpensive reagents, and recovered by filtration of the reaction solution and recycled at least 8 times without significant loss of activity.